Implementation of new techniques for diagnostics in quarantine IAC - Negri, Barbara; Passador, Martha Maria; Uzzo , Roberta Pierry; Dudienas, Christina; Almeida, Julieta Andrea Silva de (Seven Editora, 2023)
The IAC Quarantine Complex is responsible for carrying out the quarantine of plant materials that will be introduced in Brazil by private companies or public institutions, with the objective of scientific research. The materials are analyzed for pathogenic agents, as well as sown in a greenhouse for growth analysis and to verify possible pathogen symptoms. Some viruses, bacteria, and fungi, present in imported materials, require increasingly improved diagnostic and traceability techniques. As of November 2012, implementations began to promote the development of this work within a modern structure, based on international quarantine models. Including adaptations of greenhouses, cold chambers, organization, and assembly of new laboratories for the analysis of materials, in this way, new methodologies were studied and applied, such as techniques involving molecular biology (PCR). To complement the efficiency of the analyzes carried out in plant quarantine, more specific and precise tests were developed. For better results and greater security, the analyzes are carried out within IAC Quarantine complex. DOI:https://doi.org/10.56238/interdiinovationscrese-033